SPS/TBT Halal Certification and SME Export Performance: Implications for Global Market Access (International Journal of Economics and Management Research, 2026)
Indonesian SMEs face significant obstacles in penetrating the global market due to differences in halal certification standards across countries, which create high compliance burdens, both in terms of costs, process duration, and limited cross-jurisdictional recognition. These obstacles are not only administrative but also have a direct impact on export performance, particularly in terms of lead time, volume, and delivery reliability. This article aims to analyze halal certification within the framework of the WTO's Sanitary and Phytosanitary Measures (SPS) and Technical Barriers to Trade (TBT) as a dual factor, as it has the potential to act as both a barrier and an instrument for ensuring the quality of global trade. This research employs a qualitative method, utilizing a library research approach that draws on academic literature, international reports, and policy documents published between 2015 and 2025. Data were obtained from searches of reputable databases, including Scopus, Web of Science, ScienceDirect, and official documents from the WTO, BPJPH, and SMIIC/OKI. These data were then analyzed to develop a conceptual framework. The study results indicate that compliance with international halal certification significantly impacts the export performance of SMEs. The performance is primarily achieved through cost reduction mechanisms, process acceleration, cross-border recognition, and the implementation of digital traceability, thereby strengthening importer confidence. In conclusion, halal certification cannot be viewed as merely a technical issue, but rather a structural challenge that requires harmonization of standards, MRA diplomacy, and the adoption of technological innovation so that SMEs can increase their competitiveness in the global value chain.